Profil Foto Toraks Pasien Tuberkulosis Anak yang Terkonfirmasi melalui Pemeriksaan GeneXpert di RSUD Dr. Saiful Anwar - Amelia Anggia Putri; Indrastuti Normahayu (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Background: Tuberculosis (TB) in children remains challenging to diagnose due to its paucibacillary nature and non-specific clinical presentation. Aim: This study aimed to describe the chest X-ray profile of pediatric TB patients confirmed by GeneXpert examination at Dr Saiful Anwar Regional General Hospital, Malang. Methods: A descriptive observational study was conducted using retrospective data of children aged 0–18 years who underwent both GeneXpert MTB/RIF testing and chest radiography between January 2022 and February 2025. Results: A total of 73 patients were included, consisting of 47 GeneXpert-positive (64%) and 26 GeneXpert-negative (36%) cases. Among GeneXpert-positive patients, 25 (53.2%) had infiltrates, 6 (12.8%) had combined effusion and infiltrates, 1 (2.1%) had effusion + infiltrate + lymphadenopathy, 3 (6.4%) showed miliary patterns, 1 (2.1%) had bilateral effusion, 1 (2.1%) had cavitation, 1 (2.1%) had mediastinal mass with metastatic-type pneumonia, and 9 (19.1%) had normal chest radiographs. In the GeneXpert-negative group, 10 (38.5%) had clinical TB, 7 (26.9%) were non-TB, 2 (7.7%) had latent TB, 1 (3.8%) had TB relapse, 3 (11.5%) had extrapulmonary TB, 2 (7.7%) had pulmonary TB with comorbidity, and 1 (3.8%) had congenital TB. Notably, 24 GeneXpert-negative patients still received clinical TB therapy despite negative molecular results. Conclusion: Infiltrates were the most common radiological finding among GeneXpert-positive patients, while a substantial proportion had normal or nonspecific radiographs. These findings emphasize that TB diagnosis in children requires an integrated approach that combines clinical, radiological, and molecular assessments.